Role of Arts and Humanities in Medical Education - Ankita Agrawaal,; Krishna Kumar Agrawaal, (Journal of Universal College of Medical Sciences, 2025)
The integration of arts and humanities in medical education fosters emotional intelligence, critical thinking, and a patient-centered approach, essential for modern healthcare. Historically, medical training emphasized scientiﬁc rigor, leading to a detachment from humanistic aspects. The medical humanities movement, led by ﬁgures like Dr. Edmund Pellegrino, sought to reinstate compassion and ethical reﬂection in medicine. Today, medical schools incorporate humanities disciplines such as philosophy, literature, and visual arts to enhance observation skills, empathy, and communication. Studies demonstrate that humanities exposure improves diagnostic accuracy, physician-patient relationships, and clinical reasoning. However, challenges include curriculum overload, skepticism regarding relevance, and assessment difﬁculties. Future directions call for embedding humanities within core curricula, developing standardized evaluation tools, and fostering interdisciplinary collaboration. Strengthening humanities in medical education will cultivate well-rounded physicians capable of addressing the complex emotional and ethical dimensions of healthcare, ultimately improving patient outcomes and professional well-being.